Roleplays As Rehearsals for “Doing the Right Thing”—Adding Practice in Professional Values to Moldovan and United States Legal Education - Ann Juergens; Angela McCaffrey (Washington University Journal of Law & Policy, 2008)
This Essay explores lessons learned from Moldovan law students for U.S. legal education. Following this Introduction, Part I establishes context for the exchange with Moldovan law schools including some Moldovan political history. It describes the interactive exercises prepared for the exchange and how the students transformed them into a dialogue about professional values. Part II lays out research and commentary that critique legal education in the United States. In particular, the Essay notes the call for increased attention to values and to the development of responsible professional identities in law graduates. If U.S. law schools’ signature pedagogy is the case dialogue method, and if that method is well designed to teach legal analysis and doctrine, need anything be added in the first year to begin to integrate the values of the profession? Part III proposes that the answer to that question is yes, and that simple interactive exercises are a straightforward way to add values and skills exploration in first-year courses. The addition of brief roleplays does not require fund-raising or additional teachers or infrastructure. It requires only a few sheets of paper and a willingness to set aside some coverage of doctrine in exchange for discussion of values and for practice in implementing them. This section also analyzes the benefits that would be gained by the addition of short simulations into first-year courses. Part IV sketches specific steps for implementing roleplays in the first-year curriculum and provides a sample for experimentation. The Essay concludes by encouraging the use of roleplays from the first year of law school so as to include rehearsals in implementing core professional values to the traditional teaching of legal analysis.
Keywords: Clinical legal education; Legal ethics – Study & amp; teaching; Comparative law; Legal ethics; United States. Agency for International Development; Legal education; Teaching methods; Moldova; United States